Law Education To Prevent Money Politics: A Systematic Literature Review - Rahmatsyah, Rahmatsyah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
Money politics in the organization of general elections persists through the utilization of diverse strategies. Various issues arise during elections, including the prevalence of money politics, as money holds fundamental importance in human life. The most straightforward approach to undermining the integrity of an election is to manipulate voters into selecting a specific candidate exclusively based on financial considerations. In order to address the issue of money politics among the public during campaigns, quiet periods, and voting, the solution lies in providing law education. The objective of this study is to examine the field of law education in order to mitigate the occurrence of corrupt practices involving the use of money in politics. In order to accomplish this objective, this study employed a systematic literature review. The findings demonstrate that law education is efficacious in deterring corrupt practices in politics, as it aligns with the fundamental tenet of human development through education. Regulations on law education should be enforced to combat the issue of money politics in general elections. This enforcement should not only apply to individuals directly involved in money politics but also to all parties, including those who provide intellectual support.